THE DEVELOPMENT OF EMIP (ENGLISH MODUL INTERACTIVE POWERPOINT) TO IMPROVE STUDENTS’ LEARNING OUTCOME - Nusi, Ahmad; Limba, Paulina; Abrahamsz, Metty; Marantika, Mey (TELL - US JOURNAL, 2021)
This study preciously aims to elucidate the development of EMIP (English Module Interactive PowerPoint) to improve students’ learning outcomes, staff of general affairs, at Ambon State Polytechnic. This study used research and development (R&D), encompassing of the preliminary study, model development and model testing. The results of this study were obviously eligible based on the development steps.  The first results of media and material validation were shown with average score of 78,8% and 86,2% respectively. The second result, the staff general affairs' responses to EMIP (English module interactive PowerPoint) on small-scale with scored 80.75% and large-scale trials obtained a score of 84%. Furthermore, based on the value obtained, the EMIP (English module interactive PowerPoint) was feasible (very valid) to be implemented to the staff general affairs students. Referring to the test results of the staff general affairs students learning on small-scale result, it briefly showed that 62% of students totally passed with the score 74. Moreover, on a large-scale result, 100% of the students passed and scored 75. Finally, it can be concluded that the development of EMIP (English module interactive PowerPoint) is appropriate for staff general affairs at Ambon State Polytechnic.